Verrucous leukoplakia of the red border caused by the use of IQOS heated tobacco product (a case report) - H. I. Makurina; O. I. Мakarchuk; I. P. Dmytrenko; A. V. Holovkin; I. А. Sokolovska; A. S. Chornenka (Zaporožskij Medicinskij Žurnal)
The aim. To analyze possibility of development and describe the clinical case of the red border verrucous leukoplakia caused by the use of IQOS heated tobacco product and HEETS sticks and propose personalized clinical, diagnostic and therapeutic algorithm of a patient management.